Microscopic pore and fracture evolution characteristics and influencing factors during imbibition process of shale reservoirs: a case study of the first section of the first member of Longmaxi Formation, western Chongqing area, Sichuan Basin - Ji'an QIAN; Yuqiang JIANG; Tongtong LUO; Yixiao YANG; Yonghong FU; Weiming CHEN; Chaoya SUN; Zhanlei WANG (Shiyou shiyan dizhi)
Hydraulic fracturing has become an important means for shale gas exploration. Understanding the evolution characteristics and influencing factors of pores and micro-fractures during the imbibition process in shale reservoirs is crucial for optimizing post-fracturing production enhancement measures. This study focuses on the black shale at the base of the first section of the first member of the Longmaxi Formation (Long 1-1 sub-member), the main production layer in the Dazu area, western Chongqing area of the Sichuan Basin. Argon ion polishing and field-emission scanning electron microscopy (FE-SEM) experiments were conducted at fixed sites to observe the evolution pattern of microscopic pores and fractures in shale reservoirs at various stages of water imbibition process. The findings revealed: (1) After water imbibition for 7 days, organic pores at the edges of organic matter exhibited varying degrees of reduction, while the internal pore shapes and sizes remained largely unchanged. (2) Intragranular dissolution pores and intergranular pores exhibited noticeable dissolution effects, resulting in mineral particle dissolution and detachment, which increased the leakage area for shale gas. (3) The water imbibition did not induce a significant amount of new micro-fractures. Instead, it extended existing micro-fractures, with the fracture width expanding by 5 to 10 times after imbibition for 14 days. (4) The surface porosity of the shale reservoir reached its peak value at day 7 of water imbibition. After 7 days, due to the continuous swelling of clay minerals, micro-fracture widths experienced varying degrees of reduction. (5) The intensity of pore and fracture expansion in shale reservoirs was primarily affected by mineral composition and pore permeability properties. Higher contents of unstable minerals and brittle minerals with larger particle sizes led to more pronounced pore expansion effects, which were conducive to post-fracturing shale gas seepage.